From employee representation to problem-solving: Mainstreaming OHS management. (August 2019) - Hasle, Peter; Seim, Rikke; Refslund, Bjarke
The role of occupational health and safety representatives is changing. A study in 60 Danish enterprises indicates that representation, and especially negotiation on behalf of colleagues, has diminished. The work environment is mainstreamed in many enterprises and is rarely an area of conflict. The role of OHS representatives has accordingly changed to focus on solving specific problems in the workplace as an integrated part of daily operations. Both management and colleagues consider the OHS representatives as a resource that can be utilized to manage the work environment. The consequences of this development for the employees may be a stronger joint management–employee effort to improve the work environment, but also management domination and an accordingly weaker employee voice in some companies.